Systematic Literature Review (SLR) Computational Thinking Learning Science in the Period 2012 - 2021 - Suharto, Hari (Journal of Educational Technology and Instruction, 2022)
The study review of the literature systematic displays an overview of research on computational thinking in learning science in the period 2012 to 2021. In the process of selection of data in this study using a flow diagram of a Prism that can show the activity of the inclusion and exclusion of the search results data. The search is performed through the database of Springer to establish some inclusion criteria. The research variables analyzed include the distribution of publications per year, the frequency of the emergence of the term “computational thinking” in the title of the document. The number of authors publishes computational thinking year, the country's most productive research in computational thinking, as well as the number of citations in the research. The results show the publication of the study of computational thinking, the frequency of the emergence of the term computational thinking on the title of the study as well as the author of the most there in 2020, whereas in the period 2012 to 2021 the state the most to contribute in the research of computational thinking, i.e. the USA as well as publisher of research in computational thinking the most is Journal of Science and Technology which has published research in computational thinking by 56 times in one decade